Penerapan Konseling Individu Dengan Pendekatan Cognitive Behaviour Therapy Dalam Mengatasi Quarter Life Crisis (Studi Kasus Pada Klien ‘A’ Mahasiswi Fakultas Dakwah Dan Komunikasi UIN Raden Fatah) - Ayu Puteri Anrie; Kusnadi; Neni Noviza (CV. ITTC INDONESIA, 2023)
The purpose of this study was to describe the quarter life crisis and the application of the cognitive behavior therapy or CBT approach in dealing with the quarter life crisis that occurred in client 'A'. This study uses a qualitative research method with a case study research design. This research is in the form of qualitative data with primary and secondary data sources. Data collection techniques in this study were interviews, observation and documentation. The subject of this research is client 'A' and as a resource person is 'P' the younger brother of client 'A' who is also a student at UIN Raden Fatah. Data analysis techniques used are pattern matching, explanation and time series analysis. The results of the study regarding the description of the quarter life crisis experienced by client 'A' before the cognitive behavior therapy approach was applied, namely indecision in making decisions, worrying about interpersonal relationships, feeling anxious, feeling worried about the future, feeling depressed, negative self-assessment, feeling trapped in a situation difficult and feeling hopeless. In its application, counseling is carried out through four stages, namely in the first stage building relationships with clients and determining goals and what are their expectations, the second stage is identifying problems and clarifying counseling goals, the third stage is facilitating counseling changes by applying the cognitive behavior therapy approach, the fourth stage is evaluating and termination, namely the joint conclusion of the counseling results, strengthening the client's generalization and ending the counseling process. Strengthening generalizations in which the researcher asks client 'A' to express his thoughts and how he views the problems he faces so as to create more advanced patterns of thought and behavior.